La hermenéutica y la fenomenología en la investigación en Ciencias Humanas y Sociales. (2019)
This article of reflection problematizes the relationships between phenomenology and hermeneutics as epistemic places of research work through a documentary approach built in two phases. First, the text reflects on the terminological use present in the paradigms, approaches, epistemological perspectives and research methods, thereby identifying that there is no unique criteria in its references and approaches in the research methodology treaties analyzed. In the same way, it is evident that there are methodological proposals that include phenomenology and hermeneutics in a complementary, articulated or isolated way without allowing precise places of unders-tanding that allow placing their application in research. Based on the foregoing, the second phase proposes an individual approach to the background and understandings of phenomenology and hermeneutics, identifying particularities that characterize them, possible theoretical-practical differences and approaches that can be establi-shed for their relevance from the framework Epistemic and methodological research in social human sciences.